2021
DOI: 10.3389/fped.2021.619899
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum C1q Levels in Children With Sepsis

Abstract: Objective: To analyze the serum complement C1q levels in children with sepsis, and explore the suggestive effect of serum C1q levels on the condition of children with sepsis.Methods: The clinical and laboratory data of children with sepsis (n = 95) and healthy children (n = 71) in Renmin Hospital of Wuhan University from January 2019 to October 2019 were collected, and each index of the two groups was compared. Then we divided children with sepsis into three subgroups based on the Pediatric Critical Illness Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In a previous study, nevertheless, an increase of serum C1q in children with sepsis was observed. 13 We believed that there were several reasons: Firstly, the immune system of children was very different from that of adults, which would cause the response and regulation of inflammation to be different; Secondly, we observed that the main pathogen of infection in children with sepsis was mycoplasma in previous studies, and there were reports in the literature indicated that children with mycoplasma infection had elevated other complement components, 23 we guessed that C1q was also be elevated. The main pathogens in adult patients with sepsis in this study were bacteria and fungi.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study, nevertheless, an increase of serum C1q in children with sepsis was observed. 13 We believed that there were several reasons: Firstly, the immune system of children was very different from that of adults, which would cause the response and regulation of inflammation to be different; Secondly, we observed that the main pathogen of infection in children with sepsis was mycoplasma in previous studies, and there were reports in the literature indicated that children with mycoplasma infection had elevated other complement components, 23 we guessed that C1q was also be elevated. The main pathogens in adult patients with sepsis in this study were bacteria and fungi.…”
Section: Discussionmentioning
confidence: 98%
“…12 Although there are many studies on the role of complement system in sepsis in recent years, there is only one simple report on the role of C1q in children with sepsis. 13 C1q is also an important component of complement system, unlike most other complement proteins derived mainly from liver, C1q is mainly synthesized by macrophages. 14 It can regulate a variety of immune cells and plays an important role in maintaining autoimmune tolerance and regulating inflammatory response.…”
Section: Introductionmentioning
confidence: 99%